Gene expression profiling of loss of TET2 and/or JAK2V617F mutant hematopoietic stem cells from mouse models of myeloproliferative neoplasms - Kameda, Takuro (Genom Data, 2015)
Myeloproliferative neoplasms (MPNs) are clinically characterized by the chronic overproduction of differentiated peripheral blood cells and the gradual expansion of malignant intramedullary/extramedullary hematopoiesis. In MPNs mutations in JAK2 MPL or CALR are detected mutually exclusive in more than 90% of cases [1], [2]. Mutations in them lead to the abnormal activation of JAK/STAT signaling and the autonomous growth of differentiated cells therefore they are considered as “driver” gene mutations. In addition to the above driver gene mutations mutations in epigenetic regulators such as TET2 DNMT3A ASXL1 EZH2 or IDH1/2 are detected in about 5%–30% of cases respectively [3]. Mutations in TET2 DNMT3A EZH2 or IDH1/2 commonly confer the increased self-renewal capacity on normal hematopoietic stem cells (HSCs) but they do not lead to the autonomous growth of differentiated cells and only exhibit subtle clinical phenotypes [[4], [6], [7], [8],5]. It was unclear how mutations in such epigenetic regulators influenced abnormal HSCs with driver gene mutations how they influenced the disease phenotype or whether a single driver gene mutation was sufficient for the initiation of human MPNs. Therefore we focused on JAK2V617F and loss of TET2—the former as a representative of driver gene mutations and the latter as a representative of mutations in epigenetic regulators—and examined the influence of single or double mutations on HSCs (Lineage(−)Sca-1(+)c-Kit(+) cells (LSKs)) by functional analyses and microarray whole-genome expression analyses [9]. Gene expression profiling showed that the HSC fingerprint genes [10] was statistically equally enriched in TET2-knockdown-LSKs but negatively enriched in JAK2V617F–LSKs compared to that in wild-type-LSKs. Double-mutant-LSKs showed the same tendency as JAK2V617F–LSKs in terms of their HSC fingerprint genes but the expression of individual genes differed between the two groups. Among 245 HSC fingerprint genes 100 were more highly expressed in double-mutant-LSKs than in JAK2V617F–LSKs. These altered gene expressions might partly explain the mechanisms of initiation and progression of MPNs which was observed in the functional analyses [9]. Here we describe gene expression profiles deposited at the Gene Expression Omnibus (GEO) under the accession number GSE62302 including experimental methods and quality control analyses.